Study of knowledge, attitude and practice of self medication among health care workers at MC Gann Teaching District hospital of Shivamogga, India - Hanumaiah, Vedavathi; Manjunath, Harini (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Healthcare workers gain adequate knowledge related to medications used in treating illness from their work experiences which influences self medication practices. Methods: The present study was conducted in N=150 healthcare workers, divided into 2 groups with group I (nursing staff) and group II (paramedical staff) with 75 participants in each group. Data related to self medication was obtained from a pretested validated semi structured questionnaire either in Kannada or English. The responses were compared between each group with chi square test. P value ≤0.05 was considered significant. All statistical analysis was conducted with SPSS 16. Results: The mean age (mean±SD) of the participants in group I and group II is 31.79±8.309 and 34.15 (±8.168) respectively with p =0.081. The prevalence of self medication was 100% in both the groups. Both the groups knowledge related to the definition of self medication was similar (group I 63 (84.0%) and group II 62 (82.7%) p = 0.900). Group I believes that self medication is entirely safe compared to group II which was statistically significant (group I 66 (88.7%) and group II 46 (61.3%) p=0.029). Most common drugs used for self medication was NSAIDS (non steroidal anti-inflammatory drugs) in both the groups being 75 (100%). Antibiotics was used by 26 (2.66%) in group I and 14 (18.66%) in group II. Conclusions: Self medication practice is highly prevalent in the healthcare workers, who also influence the other populations to practice self medication. Practicing responsible self medication is more appreciable.